-3(2t+3)=-33

Simple and best practice solution for -3(2t+3)=-33 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(2t+3)=-33 equation:


Simplifying
-3(2t + 3) = -33

Reorder the terms:
-3(3 + 2t) = -33
(3 * -3 + 2t * -3) = -33
(-9 + -6t) = -33

Solving
-9 + -6t = -33

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '9' to each side of the equation.
-9 + 9 + -6t = -33 + 9

Combine like terms: -9 + 9 = 0
0 + -6t = -33 + 9
-6t = -33 + 9

Combine like terms: -33 + 9 = -24
-6t = -24

Divide each side by '-6'.
t = 4

Simplifying
t = 4

See similar equations:

| 85f=685 | | 5v+x=w^2 | | 15p-5p+4=9 | | -10(s+1)=51 | | 0.72*c=7.5 | | 5x-3+2x=7x+7 | | 48/-16= | | 5x-1=231 | | 3+2(5x+6)=5 | | 5(4s+6)=130 | | h-10=27 | | 8x-19=4-7x | | -1470=-5x-210 | | 8(2l+7)=72 | | -(3+6)+2x=-(6+2)-3.3 | | 14z=18+12z | | -30-29= | | 5x+7=6z | | 12[x]1/3 | | 2y-3=5-s | | 14z=18+12m | | x^2+ab-ax-bx=0 | | 0=-5x-210 | | 2x+1=52 | | (u-8)*10=20 | | 2(-13)=4(16-u) | | 7+h=23 | | 8-c=(-12)-3c | | 4(x-2)+2=14 | | z-2=35 | | 30x=240 | | 36/12=x/3 |

Equations solver categories